(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the tanning of rabbit skins, the stages of the tanning process and the chemicals used in this process, as well as the results of a study of the physicochemical properties of the skin. The content of moisture, ash, protein and oil in the skin is analyzed.